Antibacterial Effect of Honey Against Pseudomonas aeruginosa in Chronic Suppurative Otitis Media Patients and ATCC Bacterial Strains in Vitro - Nasution, Andi Imam Buchari; Zahara, Devira; Asroel, Harry Agustaf (Jurnal Biologi Tropis, 2025)
Pseudomonas aeruginosa and Staphylococcus aureus are common causative bacteria in Chronic Suppurative Otitis Media (CSOM). Honey, as a natural substance, has shown antibacterial activity. To evaluate the antibacterial effect of honey at different concentrations on P. aeruginosa (clinical isolates and ATCC 27852) and S. aureus (ATCC 29213) compared to ofloxacin. An experimental in vitro study using post-test only design was conducted. Bacterial isolates from CSOM patients and ATCC strains were exposed to honey at concentrations of 60%, 70%, 80%, 90%, and 100%. Zone of inhibition was measured using the agar diffusion method. Honey exhibited significant antibacterial activity against all tested bacteria. The highest inhibition zones were observed at 100% concentration. Ofloxacin showed greater inhibition than honey in general, but honey still demonstrated moderate to strong activity. Honey has potential as a natural antibacterial agent against P. aeruginosa and S. aureus, and may serve as an alternative or adjunct treatment for CSOM.